The formation of the entrepreneurial climate: problems and contradictions - O.I. Divichenko (Известия высших учебных заведений. Поволжский регион: Общественные науки, 2022)
Background. The processes of the Russian public’s transformation, the instability of socio-economic relations, formation of factors of turbulence in the development of socio-economic society have initiated increased public attention to entrepreneurship as a separate indicator of the well-being of society. The purpose of this research is to consider a conceptual approach to the study of entrepreneurship, in particular the content of the con-cept of “entrepreneurial climate”, as well as to present the results of a sociological study aimed at identifying the current state of the entrepreneurial climate of the Belgorod region, identifying the main problems and contradictions that hinder entrepreneurial activity. Materials and methods. The realization of research tasks is achieved on the basis of scien-tific analysis and synthesis of a wide sources’ range, including scientific and periodical literature on the problems of research, as well as the questionnaire method. Results. The role of entrepreneurship in general and the entrepreneurial climate in the system of public relations is determined, the complex of regional problems of formation and deve-lopment of entrepreneurship is considered. Conclusions. Systematic monitoring of the cur-rent problems of the formation of the entrepreneurial climate will allow, first of all, to actualize the problematic vectors of individual directions of entrepreneurship development in the region and direct the locus of attention to their solution.